Enhancing arsenate removal efficiency using seawater bittern-derived MgO nanoparticles/PVDF-HFP electrospun nanofiber composites - Rinovian, Asnan; Muhamad Nasir; Zulfikar, Muhammad Ali; Purwajanti, Swasmi; Nugraha; Handayani, Nurrahmi; Suradharmika, I Gusti Agung; Dara, Fitri (Penerbit Universiti Kebangsaan Malaysia, 2023)
MgO nanoparticles (MgO NPs) incorporated PVDF-HFP nanofibers have been synthesized using the electrospinning method to remove arsenic from polluted water. MgO nanoparticles were synthesized from seawater bitterns and used as magnesium precursors. The synthesized materials were characterized using various techniques, and their adsorption capacities were evaluated against arsenic under different conditions.The results showed that the maximum adsorption for As(V) adsorption was 41.47 mg g -1 for PVDF-HFP/MgO 30% (w/w), which equals 179.69 mg g -1 based on the weight of bare MgO NPs and achieved at pH 11, a contact time of 420 minutes, and an adsorbent weight of 0.0125 g. Incorporating MgO NPs into the nanofiber matrix can enhance its stability, further increase the adsorption capacity. This study demonstrates the potential of using PVDF-HFP/MgO nanofiber composites to treat arsenic-containing wastewater and further provide commercial benefits for seawater bitterns by serving as a precursor for producing functional nanomaterials.